Improving the thermal performance of flat-plat solar collector using nanofluid as a working fluid - Khaldo, Osama (Latakia University Journal -Engineering Sciences Series, 2025)
The research aims to improve the thermal performance of a flat-plate solar collector by using nanofluids as a heat transfer medium, contributing to an increase in the efficiency of solar systems. Two identical solar collectors were fabricated using aluminum and copper components, insulated with transparent glass. The collectors were tested under identical climatic conditions in Latakia city during the summer and autumn of 2023. The results demonstrated that the nanofluid, primarily composed of copper oxide nanoparticles (CuO) at a concentration of 0.2%, improved the outlet fluid temperature by 13% compared to using water alone. The tests included monitoring solar radiation intensity and temperature changes at the optimal flow rate, which was determined to prevent energy loss due to excessive or insufficient flow. The results also showed that the outlet temperature of the nanofluid was higher than that of the traditional fluid, enhancing the thermal performance of the solar collectors. The conclusions indicated that adding copper oxide at a specified concentration significantly improved thermal conductivity and efficiency. However, increasing the concentration of nanomaterials leads to agglomeration, reducing the thermal transport efficiency. The study recommended conducting future research to explore other types of nanofluids to further enhance performance. This research provides a scientific model for improving the thermal efficiency of solar collectors using nanotechnology, contributing to the promotion of solar energy as a sustainable energy source.